A meta-analysis of photocatalytic performance and efficiency of bismuth oxide (BiO2_x). (1st November 2021) - Dar, Afzal Ahmed; Shakoor, Awais; Niazi, Nabeel Khan; Tufail, Muhammad Aammar; Syed, Jawad Ali Shah; Sarfraz, Muddassar; Faheem, Muhammad; Shabbir, Sadaf; Haq, Inzamam ul; Wang, Chuanyi
Abstract: Semiconductor-based photocatalysis is a promising technology for the future of solar fuel production. However, the solar energy conversion efficiency is not much studied. Hence it is important to create innovative semiconductor photocatalysts for environmental rehabilitation and energy production. Recently, bismuth-based oxide (BiO2-x ) has seen attention due to its narrow bandgap, high number of defect sites and its unique layered structure. In this study, we discussed photocatalytic performance of the BiO2-x catalyst and its derived emergent forms through meta-analysis of data published between 2015 and 2020, allowing to explore the best available technologies prevalent for industrial applications. Various studies including pure BiO2-x, doped BiO2-x and BiO2-x based heterogeneous nanocomposites were selected through PRISMA guidelines for critical discussion. This study has been conducted with the aim of narrowing out various techniques of preparation of BiO2-x related photocatalysts, thus allowing to select the most efficient technique. The qualitative review and meta-analysis of 17 out of 21019 studies revealed that, BiO2-x despite being an excellent photocatalyst in the UV–Vis-INR range, still underperforms in comparison to its derivatives. These synthesized subsidiaries include BiO2-x based nanocomposites with a thin layer structure, doped with various elements, or coupled with other semiconductors. The current meta-analysis of data is the first of its kind and a step forward in analyzing the potential of BiO2-x and its derivatives quantitatively and extensively. It implies the future research directions that can be adopted for development of the improved techniques of preparing photocatalysts made up of BiO2-x and its derivatives. Graphical abstract: Image 1